Magallanes Sheep Farming - Radic Schilling, Sergio Javier; Francisco Sales; Raúl Lira; Muñoz Arriagada, Rene Santiago; Paulo Corti; Nilo Covacevich; Jorge Ivelic-Sáez; Iván P. Ordóñez; Vidal Ojeda, Osvaldo Javier; Echeverria Perez, Ricardo Andres; Camila Sandoval (My University, 2022)
The Magallanes region in Chilean Patagonia encompasses 13 million hectares with approximately 3.6 million used for agricultural and livestock systems. This portion is located to the east of the Andean Mountain chain in the rain shadow zone, with annual precipitation increasing along an east to west gradient from 200 to almost 1,000 mm. To fully describe sheep farming in the Magallanes region, many topics need to be addressed, including sheep production and management, existing vegetative communities, livestock-wildlife interactions, and economic diversification into agritourism and another sheep industry products. All these give shape to the story of the development of sheep farming in Magallanes, which is important at the regional and national level. Three key points are identified that together can lead to a successful future for the industry: sustainable management, human resources and the market.
Keywords: None